Implementasi “The Flash” New Character Building Dalam Upaya Meningkatkan Revolusi Mental Karyawan PT. Swabina Gatra (International Forum of Researchers and Lecturers, 2024)
In the current global era, character building is needed in all fields, especially in companies that want their human resources to be better at work.